Distribution of chemical elements in the snow at the site S25 in Antarctica - Kanamori, Satoru; Kanamori, Nobuko; Osada, Kazuo; Isa, Eriko; Nishikawa, Masataka; Nishio, Fumihiko; Watanabe, Okitsugu (National Institute of Polar Research, 1989)
P(論文) The firn block samples, being 50cm deep and covering nearly one-year formation, were taken at the site S25 on Antarctic ice sheet near Syowa Station. The vertical distribution of Cl, Na, and SO_4 showed high and nearly constant level in the upper 37.5cm (766 ppb, 425 ppb, and 119 ppb, respectively) which accumulated within the period from the autumn of 1985 (based on the distribution of major elements) to early summer of 1986 when high influence of marine air is expected. On the other hand, very low concentration levels of these species (219 ppb, 117 ppb, and 64 ppb, respectively), but with high SO_4/Na ratio, were found in the lower 12.5cm layer which accumulated in the late summer of 1985 when concentration of SO_4 aerosols is high. NO_3 showed several peaks in the upper 37.5cm and K and NH_4 low level. The mean concentrations of Al, Fe, Zn, and Cu were 323 ppt, 251 ppt, 435 ppt, and 118 ppt, respectively. These concentration levels are much higher than those reported for snow and ice from inland area but comparable with those measured at the Syowa Station and the site S16 near the site S25. The metal organic compounds of these heavy metal elements were firstly determined in the Antarctic snow and their contributions to the total amounts were significant. This new finding, in association with the observation that the organic heavy metal compounds has also been found in atmospheric aerosols collected in the Antarctic air as well as in the marine air, suggests their new possible origin and path to the Antarctica. departmental bulletin paper